Backward Pass
Update equation for the hidden-to-output weights
The update equation for the hidden-to-output weights is derived as
wij′(new)=wij′(old)−η∂wij′∂E=wij′(old)−ηejhi(1)
or equivalently
v¯wj′(new)=v¯wj′(old)−ηejh¯(2)
The derivative of E to hi is repeated as
∂hi∂E=j=1∑V∂uj∂E∂hi∂uj=j=1∑Vejwij′(3)
and
hi=C1m=1∑Cwcmi, i=1,2,⋯,N(4)
By using (3) and (4), the derivative of E to wki is
∂wki∂E=∂hi∂E∂wki∂hi=C1j=1∑Vejwij′(5)
by which, the update equation for the input-to-hidden weights is derived as
wki(new)=wki(old)−η∂wki∂E=wki(old)−Cηj=1∑Vejwij′(old)(6)
or equivalently
v¯wk(new)=v¯wk(old)−Cηj=1∑Vejv¯wj′(old), wk∈Cx(wjo)(7)